The Determinants of Effective Islam-Based Junior High School in the Regency of Purbalingga - Wahyudhiana, Wahyudhiana; Rokhman, Fathur; Soesanto, Soesanto; Kardoyo, Kardoyo (Universitas Negeri Semarang, 2018)
This study is based on the performance of education supervisors, the performance of madrasah principals, the performance of professional teachers, and the performance of madrasah committees, which synergize into the model of effective madrasah tsanawiyah in Purbalingga District. The problems raised in this study are (1) whether the relationships among the variables affecting the effectiveness of madrasah can be empirically tested and (2) how the contribution of education supervisors, heads of madrash, professional teachers, and madrasah committees to the quality of madrasah processes and effectiveness. This research was designed as a correlational study using path analysis. The population of this study was all professional teachers in 31 of 39 public and private MTs accredited